Study of the impact of environmental pictures on emotional aspects - Sánchez Miranda, Martha Patricia (2015)
The present research examined emotions that automatically and implicitly trigger pictures of nature and the city, with the affective priming technique, and determined if the same phenomenon that has been studied in unimodal experiments was replicated in cross modality experiments. The sample included 57 psychology students from a Mexican public university who were exposed to images of natural and urban environments. They used words with positive and negative emotional connotations. The results are similar to other research studies, and indicate that there are two types of participants, and not all participants displayed positive emotions towards nature. The findings are discussed in terms of the cognitive mechanisms of the technique.